2022
DOI: 10.6007/ijarbss/v12-i1/12282
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Faced by Disabled Students in Online Learning during the COVID-19 Pandemic

Abstract: The Covid-19 pandemic has brought changes to the scenario of teaching and learning in schools and higher institutions of education. The shift from face-to-face traditional mode to online platforms has brough many challenges along with it. This 'new norm' of pedagogy has also posed challenges to disabled students in higher learning institutions across Malaysia especially when using online platforms to study. Therefore, the purpose of this study was to investigate the mental and emotional challenges and learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…Furthermore, the lack of feedback from their teachers made the learning process much more difficult because the special needs students primarily depended on the teachers' and colleagues' feedback during their educational activities. Similar issues were noticed in recent studies (Bakaniene et al, 2022;Paramasivam et al, 2022), wherein the special needs students reported mental stress challenges because they were not familiar with online teaching mediums such as Skype, Zoom and Google Meet. Further, they were not familiar with other modern electronic gadgets used for online learning.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Furthermore, the lack of feedback from their teachers made the learning process much more difficult because the special needs students primarily depended on the teachers' and colleagues' feedback during their educational activities. Similar issues were noticed in recent studies (Bakaniene et al, 2022;Paramasivam et al, 2022), wherein the special needs students reported mental stress challenges because they were not familiar with online teaching mediums such as Skype, Zoom and Google Meet. Further, they were not familiar with other modern electronic gadgets used for online learning.…”
Section: Discussionsupporting
confidence: 76%
“…Further, a considerable number of teachers across the globe, including those in the education sector in the United Arab Emirates (UAE), were not prepared enough for the drastic transition from face-to-face teaching to the online mode of instruction (Erfurth & Ridge, 2020;Dawson & Heylin, 2022;Maatuk et al, 2022). The requirements for inclusive education, which teachers achieved through their direct physical help in the classroom, became a challenge for teachers with the online mode of instruction (Yazcayir & Gurgur, 2021;Paramasivam et al, 2022). In the UAE context, there is a dearth of studies related to inservice teachers' preparedness and the challenges they face in inclusive education.…”
Section: Introductionmentioning
confidence: 99%
“…Teachers in the current study also reported that the students with visual impairment face difficulty in accessing the lectures during online teaching. It was revealed through interviews that sudden introduction of online classes for these students, was an obstacle for which they were ill-equipped (Paramasivam et al, 2022).…”
Section: Discussion and Analysismentioning
confidence: 99%
“…The disabled students must overcome emotional setbacks, isolation, exacerbated mental health, lack of confidence and anxiety, so they can effectively familiarize to the new learning challenges to which they have been newly introduced. Some challenges related to the topics mentioned earlier include, the lack of communication between the teachers and students, uninterrupted internet connection and the need to adapt to a completely new environment (Paramasivam et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation